2012
DOI: 10.1159/000334837
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Serrated Adenocarcinoma Defined by Mäkinen in Dukes’ B Colorectal Carcinoma

Abstract: Objective: Serrated adenocarcinoma (SAC), proposed as a new pathologic type, arises predominantly in the right side of the colon and has a poorer prognosis than conventional colorectal carcinoma. The prognosis of colorectal carcinoma is variable in Dukes’ B, so the aim of this study was to determine whether or not SAC has a poor prognosis in Dukes’ B. Methods: The study group comprised 64 patients who underwent surgery for colorectal carcinoma. We undertook a statistical analysis of the association of SAC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…In contrast with previous conventional CRC findings (most are non-MAC) [18, 19], patients in our study who had colorectal MACs with SAC morphology exhibited improved relapse-free survival, and this was significant in AJCC stage III MAC patients. SAC morphology was associated with proximal cancer location and CIMP-positive status, which were favorable prognostic factors in our analyses.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with previous conventional CRC findings (most are non-MAC) [18, 19], patients in our study who had colorectal MACs with SAC morphology exhibited improved relapse-free survival, and this was significant in AJCC stage III MAC patients. SAC morphology was associated with proximal cancer location and CIMP-positive status, which were favorable prognostic factors in our analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…First, we did not include non-MACs for comparison, as our findings on the prognostic implications of SAC morphology contradicted results from studies of conventional, mostly non-MAC, CRC [18, 19]. Second, to avoid the effect of neoadjuvant therapy in histological analyses, we excluded low rectal cancer cases, which had often undergone neoadjuvant concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serrated morphology has been associated with poor prognosis, particularly when occurring in left-sided tumors 30,31. Adenosquamous carcinoma has features of both squamous cell carcinoma and adenocarcinoma, either mixed or separate 5,32,33.…”
Section: Histopathological Variants Of Colorectal Cancermentioning
confidence: 99%
“…Although it has been generally accepted that adenoma-carcinoma sequence [2] is an important pathway in colonic carcinogenesis, recent studies revealed that DNA hypermethylation and/or BRAF mutations also play important roles in the tumor progression especially in right-sided colon carcinomas and that SSL morphologically represents a characteristic feature of a newly postulated cancerization pathway, coined “serrated neoplasia pathway” [3, 4]. Moreover, some investigators suggested that neoplastic SSL closely associated with mucinous adenocarcinoma [5], and others reported that the outcome of patients with colorectal carcinomas that featured serrated architecture was worse than that of patients with nonserrated carcinomas [6]. …”
Section: Introductionmentioning
confidence: 99%